Identification and characteristics of drug resistance and genotypes of methicillin-resistant Staphylococcus aureus isolated from intensive care units at obstetrics & gynaecology departments: a retrospective analysis - Zhonghua Huo; Binxian Li; Xue Meng; Peiyao Li; Mingcheng Li (Clinical and Experimental Obstetrics & Gynecology, 2022)
Background: The aim of this study was to investigate the prevalence and characteristics of SCCmec genotypes and drug resistance of methicillin-resistant Staphylococcus aureus (MRSA) isolated from intensive care units (ICU) at obstetrics & gynaecology departments in a tertiary hospital. Methods: MRSA obtained from patients admitted to the ICU were isolated and identified by using the Vitek 2 Compact System with GP21 342 cards. Antimicrobial susceptibility profiles and MRSA screening were determined by using the broth microdilution method according to CLSI guidelines. Determination of resistant genes and SCCmec genotypes were performed by multiplex PCR. Results: Of the 283 patients evaluated, 120 (42.4%) isolates were phenotypically and genotypically confirmed to be MRSA. Among 120 strains, 15 (12.5%) strains were SCCmec type II, 96 (80%) strains were SCCmec type III and 9 (7.5%) strains were undifferentiated type. All MRSA strains were recognized as multidrug resistant, exhibiting 100% resistance to cefoxitin and oxacillin, followed by erythromycin and levofloxacin (more than 80% and 90% respectively). Different SCCmec genotypes in MRAS isolates showed distinct antimicrobial agent patterns. SCCmec type II was highly resistant to clindamycin (93.3%) with lower resistance to tetracycline (26.7%) with SCCmec type III being highly resistant to gentamicin (91.7%). Undifferentiated strains were resistant to Cotrimoxazole (77.8%). There was a statistical difference among type II, type III and Undifferentiated strains (P < 0.05). Of interest, a high prevalence of resistance to rifampicin (more than 75%) was also noted in the hospital. With different SCCmec genotypes, MRSA isolates were sensitive to minocycline, quinupristin, teicoplanin, vancomycin and nitrofurantoin. Conclusions: Our data indicate that SCCmec type II and SCCmec type III of MRSA are circulating in the ICU and constitute a major source for the infection spread. It is necessary to increase surveillance of MRSA in the ICU and develop adequate infection prevention strategies.